DNP‐Supported Solid‐State NMR Spectroscopy of Proteins Inside Mammalian Cells. (19th July 2019) - Narasimhan, Siddarth; Scherpe, Stephan; Lucini Paioni, Alessandra; van der Zwan, Johan; Folkers, Gert E.; Ovaa, Huib; Baldus, Marc
Abstract: Elucidating at atomic level how proteins interact and are chemically modified in cells represents a leading frontier in structural biology. We have developed a tailored solid‐state NMR spectroscopic approach that allows studying protein structure inside human cells at atomic level under high‐sensitivity dynamic nuclear polarization (DNP) conditions. We demonstrate the method using ubiquitin (Ub), which is critically involved in cellular functioning. Our results pave the way for structural studies of larger proteins or protein complexes inside human cells, which have remained elusive to in‐cell solution‐state NMR spectroscopy due to molecular size limitations. Abstract : Eine Festkörper‐NMR‐Spektroskopiemethode zum Studium von Proteinen in eukaryotischen Zellen bei endogenem Expressionsniveau unter hochempfindlichen dynamischen Kernpolarisationsbedingungen wird vorgestellt. Der Ansatz wurde unter Verwendung von Ubiquitin demonstriert, und die Aminosäuren, die identifiziert werden konnten, sind in Rot hervorgehoben. Diese Ergebnisse ebnen den Weg für strukturelle Studien von Biomolekülen und ihren Komplexen in menschlichen Zellen mit atomarer Auflösung.